Learning Activities and Their Impact on Students' Understanding of Linear Equations in One Variable - Siti Maryam Rohimah; Darhim; Juandi, Dadang (Mathematics Education Journal, 2025)
Junior high school students often have difficulties in understanding linear equations in one variable (LEOV). Therefore, this research aimed to enhance junior high school students' understanding of LEOV by developing and implementing effective learning activities. The research was conducted as design research in three stages: preliminary design, teaching experiment, and retrospective analysis. The participants of the research were 50 seventh-grade students from two junior high schools in Bandung, Indonesia. The data collected from observations, interviews, and student worksheets were analyzed using triangulation to ensure the validity and reliability of the research. The research explored how the teacher explained LEOV in four meetings and how they contributed to students’ understanding, where the first meeting dealt with open sentences, closed sentences, and the definition of LEOV from the context of distance and displacement, the second focused on solving LEOV from the context of two passing trains, and third focused on fractional LEOV from the context of jogging, and the fourth provided the students an opportunity to apply the LEOV concept from a dynamo-powered toy car simulation. The implication of the research is that teachers can significantly improve students' understanding of LEOV by implementing effective learning activities as identified here.